Enhancement of solubility and dissolution of glipizide by solid dispersion (kneading) technique - Choudhary, D; Kumar, S; gupta, G D (Asian Journal of Pharmaceutics (AJP), 2014)
Glipizide is a poorly water-soluble (BCS class II) antidiabetic drug. Due to the poor water solubility of this drug, its bioavailability is dissolution rate-limited. The purpose of this study was is to increase the solubility of Glipizide (GZ) in aqueous media by solid dispersion (SDs) technique with Poloxamer (PXM) 188 and Poloxamer (PXM) 407 by using the kneading method.The GZ-PXM solid dispersion system was characterized by dDifferential scanning calorimetry (DSC), X-ray powder diffraction (XRD) analysis, Fourier transform-infrared spectroscopy (FT-IR) and Scanning electron microscopy (SEM), and in vitro dissolution studies. No chemical interaction was found between GZ and PXM 188 or PXM 407. The results from DSC, XRD and SEM studies show that PXM 188 or PXM 407 inhibits the crystallization of GZ. The SDs prepared in this study were found to have better dissolution rates in comparisoncompared to intact GZ and physical mixture of PXM 188 or PXM 407 and GZ. It was found that the optimum weight ratio for drug: Carrier is 1:5 for PXM 188 and 1:6 for PXM 407.